Fishbone Flour Derived from Indian Mackerel (Rastrelliger Kanagurta) to Improve the Calcium and Protein Content of Fish Sausage - Alvin Wijaya; Deannisa Fajriaty; Zamzahaila Mohd Zin; Zuraidah Nasution (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2026)
Sausages are widely consumed animal-based food products valued for their convenience and desirable sensory properties. Fish sausages are increasingly popular; however, despite being derived from fish, they often have limited calcium content. This study investigated the effect of incorporating fishbone flour derived from Indian mackerel (Rastrelliger kanagurta) on the protein and calcium content of fish sausages. Fishbone flour was produced via acid extraction and incorporated into sausage formulations containing 100 g of fish meat, with three levels of addition: 0, 2.5, and 5 g. The optimal formulation was determined based on sensory evaluation, physical characteristics, and nutrient composition analysis. The results indicated that the formulation containing 2.5 g of fishbone flour provided the best overall quality and acceptability. This sausage formulation contained 64.24 g of moisture, 1.97 g of ash, 13.04 g of protein, 3.96 g of fat, 16.80 g of carbohydrates, and 165.19 mg of calcium per 100 g of product. A typical serving size equivalent to two sausages provides approximately 93 kcal. The addition of fishbone flour significantly increased the calcium content without compromising sensory quality. The resulting mackerel sausage formulation can potentially meet the nutritional criteria for labeling as a source of protein and calcium. These findings demonstrate the potential of fishbone flour from Indian mackerel as a functional ingredient to improve the nutritional value of fish-based processed products while promoting the utilization of fish processing by-products.